Brechas de equidad en la evaluación censal de estudiantes 2007-2014: tres aproximaciones a su medición - Guadalupe, César (2015)
This article discusses the evidence produced by the census-based student assessment (conducted in grade two –primary education to measure performance in relation to reading comprehension and mathematics) between 2007 and 2014 in relation to equity– related gaps regarding students’ sex; school management type (State-run; Privately-run); location (urban/rural areas); and the manner in which the provision of instruction is organised (complete/multigrade schools).